THE CORRELATION OF THERAPEUTIC COMMUNICATION WITH CLIENT TRUST AGAINST NURSES IN INPATIENT AT SARI MULIA HOSPITAL BANJARMASIN - MOHAMMAD BASIT; Rifa"atul Mahmudah (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2015)
Background: Therapeutic communication occurs when preceded by a trusting relationship between the nurse and client. In the context of nursing services to the client, the first client must believe that nurses are able to provide nursing care in dealing with complaints.Methods: The research design that used in this research is analytic survey with cross sectional approach with a total sample of 85 male and female patients which have criteria from 17-45 years old and using purposive sampling technique. Collecting data using instruments such as questionnaires therapeutic communication tools and trust client , and then analyzed using the Spearman Rank (Rho) with a significant p = 0.05.Result: The results showed therapeutic communication in the unfavorable category is 55.3% and the trust client in the unfavorable category also is 60.0%. In the analysis by Spearman Rank correlation test results obtained p = 0.009 0.05 with r = 0282 meaning have moderate strength rate.Conclusion: The Existence Of Therapeutic Communication RelationshipÂ  With Client Trust Against Nurses In Inpatient General Sari Mulia Hospital Banjarmasin.Â Keyword: Therapeutic Communication, Client Trust.